POPULASI Lamprosema indicata (LEPIDOPTERA: PYRALIDAE) PADA TANAMAN KACANG MERAH DI KECAMATAN TOMPASO DAN KAWANGKOAN KABUPATEN MINAHASA - Margareta M. Kawulusan; Odi R. Pinontoan; Mareyke Moningka; Dantje Taroreh (COCOS, 2014)
ABSTRACTMargareta M. Kawulusan. Population Lamprosema indicata (Lepidoptera: Pyralidae) to Plant in Red Beans at District Tompaso and Kawangkoan Regency Minahasa. Guidence Prof. Dr. Ir. Odi R. Pinontoan, MS as chairman, Dr. Ir. Mareyke Moningka, MS and Dr. Ir. Dantje Tarore, MS as member.This study aims to determine the symptoms and attacks on the population of L. indicata red beans crops in the district Tompaso and Kawangkoan, Minahasa regency. The study uses survey and sampling methods are purposive sampling at a predetermined location. Area is used as an observation area set at 300 m2 which is divided into five sub-plot of the observations in the form of diagonal slices. Observations on the larval population sub-plot planting beans defined five beds and beds of each plant sample was observed ten systematically determined. Observations were carried out five times at intervals of seven days in the time period of 2-3 weeks old plants. Things were observed in this study is a symptom of pest attack L. indicata larvae collected and the number of observation each time.Pests attack L. indicata encountered red bean crop farmers in the district Tompaso and Kawangkoan. Population larvae L. indicata in District Kawangkoan peak in the third observation that 6,60 in the village were in the village Kanonang Tondegesan, observation of a peak in the fourth with an average population of the same, namely 6.60. While in the District Tompaso, peak larval populations of L. indicata third at 7.00 on observations of individuals in the village Tonsewer I, a peak in the second observation with the population average of 6,80.Key words : Lamprosema indicatai, Kacang Merah, Minahasa